Thermo-Priming Mediated Cellular Networks for Abiotic Stress Management in Plants - Khan, Ambreen; Khan, Varisha; Pandey, Khyati; Sopory, Sudhir Kumar; Sanan-Mishra, Neeti (Frontiers in Plant Science, 2022)
Plants can adapt to different environmental conditions and can survive even under very harsh conditions. They have developed elaborate networks of receptors and signalling components, which modulate their biochemistry and physiology by regulating the genetic information. Plants also have the abilities to transmit information between their different parts to ensure a holistic response to any adverse environmental challenge. One such phenomenon that has received greater attention in recent years is called stress priming. Any milder exposure to stress is used by plants to prime themselves by modifying various cellular and molecular parameters. These changes seem to stay as memory and prepare the plants to better tolerate subsequent exposure to severe stress. In this review, we have discussed the various ways in which plants can be primed and illustrate the biochemical and molecular changes, including chromatin modification leading to stress memory, with major focus on thermo-priming. Alteration in various hormones and their subsequent role during and after priming under various stress conditions imposed by changing climate conditions are also discussed.